ANALYSIS OF THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND COMMUNICATION ON EMPLOYEE PERFORMANCE (CASE STUDY AT THE NATIONAL HIGHER FOUNDATION Dr. WAHIDIN SUDIROHUSODO MEDAN) - Simbolon, Sahat (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
This study aims to examine the effect of transformational leadership and communication on employee performance at the Dr Wahidin Sudirohusodo National Higher Education Foundation, Medan. The number of samples in this study were 76 respondents using simple random sampling method. This type of research is quantitative research using path analysis techniques and questionnaire data. Path analysis hypothesis test is done by using multiple linear analysis, classical assumption test and intervention test. The transformational leadership and communication variables partially show a significant effect on employee performance. Transformational leadership variables and communication simultaneously affect employee performance with a coefficient of determination of 87.8% which means transformational leadership variables, communication can explain employee performance as much as 87.8% and the remaining 12.2% is explained by other variables such as discipline, commitment, compensation and others. Transformational leadership and communication variables simultaneously affect employee performance with a coefficient of determination of 87.8% which means that transformational leadership and communication variables can explain employee performance as much as 87.8% and the remaining 12.2% is explained by other variables such as discipline, commitment. , compensation and others.